Presumed Corneal Ulcer Following Topical Use of Diclofenac Sodium in One Eyed Patient with Keratoplasty - Cumurcu, Tongabay; Gunduz, Abuzer; Mutlu, Kayhan; Cavdar, Mufide (Journal of Ocular Diseases and Therapeutics, 2014)
Purpose: To report a case with corneal ulcer after keratoplasty connected to long-term use of topical 0.1% diclofenac sodium. Methods: A 81-year-old man presented with corneal ulceration. The patient’s clinical history showed that he had keratoplasy after ocular trauma for about 10 years ago. He was using topical dexamethasone sodium phosphate 0.1% and topical diclofenac sodium 0.1% for one year. Diclofenac sodium and dexamethasone sodium phosphate were discontinued, and amniotic membrane transplantation and bandage contact lens application were performed. Results: After the amniotic membrane transplantation; at the first month, melting area disappeared, increase in corneal transparency and improvement in visual acuity was recorded. Conclusion: Use of long-term diclofenac sodium may be responsible for the corneal ulceration in our patient, and we suggest that amniotic membrane transplantation may be a good choice in similar cases.